CURRENT STATUS AND PROSPECTS FOR THE DEVELOPMENT OF VENTURE FINANCING - Sembieva L.M.,; Sujubaeva S.,; Zhagyparova A.O.,; Atirbekov A.,; Petrov A.M., (Academic Journal of Physical and Chemical Sciences, 2020)
In modern conditions, entrepreneurs directly initiating new projects, large industrial companies, and the state clearly realize that a refusal to invest in the development of innovations would mean in practice much greater financial losses. Therefore, they are following the path of creating economic mechanisms that, on the one hand, would facilitate the introduction of the latest achievements of scientific and technological progress into production, and on the other, would allow to minimize the financial risk of individual investors. One of such mechanisms is venture (risk) financing of innovations. The venture mechanism has played an important role in the implementation of many of the largest innovations in various fields of activity. At the present stage of development in the context of globalization, the economic situation of countries is increasingly dependent on the level of innovation. If several centuries ago the power of state power was determined by gold reserves, land fertility and mineral resources, in the 21st century the level of development of science and technology in the economic sector began to play an increasingly important role. As one of the reasons for limiting the volume of innovation, it is customary to attribute a lack of investment. The experience of economically developed countries shows that the development of innovative financing mechanisms from various sources (government, corporations) can solve the problem of insufficient investment. Venture financing is one of the possible mechanisms to support innovative companies. The example of Silicon Valley in California, USA, serves as a vivid example of how the formation of innovative companies in the region was largely ensured by the parallel development of venture capitalism - venture capital funds and frequent investors. The development of venture financing in Kazakhstan is considered one of the priority vectors of state innovation development, which contributes to the intensification of innovative activity and increase the competitiveness of the country's economy. The development of venture financing and venture entrepreneurship can solve a whole range of tasks that are strategically important for the implementation of positive qualitative changes in the economy. Firstly, this means an additional influx of investments, including from abroad. Secondly, there is an opportunity to revive and significantly intensify the national innovative potential, gradually turning it into the main “locomotive” of the development of the domestic economy, expanding its tax and export base. Thirdly, there will be a rapprochement between the Kazakhstani and international business environment on the basis of the most modern forms and directions of economic activity, interaction with direct developers of innovative products. With venture capital, domestic entrepreneurs receive not only Western money, but also advanced managerial experience and extensive business contacts necessary for the international commercialization of their own technological developments, while maintaining control over the company in their hands.